Heart failure complicating myocardial infarction: a report of the Peruvian Registry of ST-elevation myocardial infarction (PERSTEMI) - Chacon Diaz, Manuel (2018)
Objectives: The aim of this study is to determine the incidence, associated factors, and 30-day mortality of patients with heart failure (HF) after ST elevation myocardial infarction (STEMI) in Peru. Methods: Observational, cohort, multicentre study was conducted at the national level on patients enrolled in the Peruvian registry of STEMI, excluding patients with a history of HF. A comparison was made with the epidemiological characteristics, treatment, and 30 day-outcome of patients with (Group 1) and without (Group 2) heart failure after infarction. Results: Of the 388 patients studied, 48.7% had symptoms of HF, or a left ventricular ejection fraction <40% afterinfarction (Group 1). Age > 75 years, anterior wall infarction, and the absence of electrocardiographic signs of reperfusion were the factors related to a higher incidence of HF. The hospital mortality in Group 1 was 20.6%, and the independent factors related to higher mortality were age > 75 years, and the absence of electrocardiographic signs of reperfusion. Conclusions: Heart failure complicates almost 50% of patients with STEMI, and is associated with higher hospital and 30-day mortality. Age greater than 75 years and the absence of negative T waves in the post-reperfusion ECG are independent factors for a higher incidence of HF and 30-day mortality.